Cost-Effective and Rapid Prototyping of Pmma Microfluidic Device Via Polymer-Assisted Bonding - Sözmen, Alper Baran; Sözmen, Alper Baran; Arslan Yıldız, Ahu; Arslan Yıldız, Ahu (Springer, 2021)
Microfluidic systems are relatively new technology field with a constant need of novel and practical manufacturing materials and methods. One of the main shortcomings of current methods is the inability to provide rapid bonding, with high bonding strength, and sound microchannel integrity. Herein we propose a novel method of assembly that overcomes the mentioned limitations. Polymer-assisted bonding is a novel, rapid, simple, and inexpensive method where a polymer is solubilized in a solvent and the constituted solution is used as a bonding agent. In this study, we combined this method with utilization of several phase-changing materials (PCMs) as channel-protective agents. Glauber's salt appeared to be more suitable as a channel-protective agent compared to rest of the salts that have been used in this study. Based on the bonding strength, quality analyses, leakage tests, and SEM imaging, the superior assisting bonding solvent was determined to be dichloromethane with a PMMA concentration of 2.5% (W/V). It showed a bonding strength of 23.794 MPa and a nearly non-visible bonding layer formation of 2.83 mu m in width which is proved by SEM imaging. The said combination of PCM, solvent, and polymer concentration also showed success in leakage tests and an application of micro-droplet generator fabrication. The application was carried out to test the applicability of developed prototyping methodology, which resulted in conclusive outcomes as the droplet generator simulation run in COMSOL Multiphysics version 5.1 software. In conclusion, the developed fabrication method promises simple, rapid, and strong bonding with sharp and clear micro-channel engraving.
Keywords: Microfluidics; Rapid prototyping; Microfabrication; Laser ablation; Micro-droplet generator